The ancient world in silent cinema - Michelakis, Pantelis; Wyke, Maria (Cambridge University Press, 2013)
"In the first four decades of cinema, hundreds of films were made that drew their inspiration from ancient Greece, Rome, Egypt and the Bible. Few of these films have been studied, and even fewer have received the critical attention they deserve. The films in question, ranging from historical and mythological epics to adaptations of ancient drama, burlesques, cartoons and documentaries, suggest a fascination with the ancient world that competes in intensity and breadth with that of Hollywood's classical era. What contribution did antiquity make to the development of early cinema? How did early cinema's representations affect modern understanding of antiquity? Existing prints as well as ephemera scattered in film archives and libraries around the world constitute an enormous field of research. This extensively illustrated edited collection is a first systematic attempt to focus on the instrumental role of silent cinema in twentieth-century conceptions of the ancient Mediterranean and Middle East"--